Screening of Xanthium strumarium (IAPS) Growing on Abandoned Habitats in Khyber Pakhtunkhwa, Pakistan: Perspectives for Phytoremediation - Rafi Ullah; Nasrullah Khan; Kishwar Ali; Muhammad Ezaz Hasan Khan; David Aaron Jones (Applied Sciences, 2021)
The ecological impacts of invasive alien plant species (IAPS) are well-documented, but a dearth of studies exist concerning its economic, livelihood, biotechnological, and health risk assessment perspectives. IAPS management is currently expanding to ecological indicator and biotechnological aspects. Hence, this study aimed to investigate the phytoremediation potential, biomedical, and bio-safety applications of X. strumarium growing in different abandoned habitats in Khyber Pakhtunkhwa, Pakistan. In this study, 45 plants and soil samples were gathered from 15 abandoned sites and analyzed for Pb, Cd, Cu, and Zn concentrations; bioaccumulation (BA); and translocation factor (TF). The assayed Pb and Cd concentration was higher and above threshold in both soil–plant samples. BAF was found higher in roots than intact plants despite having a significant accumulation of Cd, Pb, and Zn, which shows high metals tolerance of this IAPS. PCA-ordination explained a high cumulative variance (98.9%) and separated roads and densely populated sites with comparatively high metals concentration, indicating the pseudometallophyte nature of X. strumarium. Soil, sand, and plant biomass were shown to be the major determinants affecting the heavy metals concentration and its phytoremediation significantly, which may be due to the soil’s metalliferous nature in the study area. This IAPS exhibited strong translocation and hyperaccumulation capacity in different functional traits with comparatively high Pb, Cd, and Zn (≥1 TF) mobility and, hence, can effectively be used for Pb phytoextraction and phytostabilization of Cd, Cu, and Zn, respectively. Likewise, several other non-spontaneous IAPS growing on such abandoned habitats might be promising for developing a reasonable strategic framework for heavy metals mitigation and health risk implications in this region.